THE REDISTRIBUTION OF THE HEIGHT RETAINING WALLS LEVELS, ITS EFFECT AT THE STRESS-STRAIN STATE OF THE SYSTEM «RETAINING STRUCTURES – SOIL MASS» - Skochko, L. O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The work of multi-level retaining walls in sandy loam soils is investigated. A numerical experiment was conducted for reveal the most rational choice of the level height at a constant total excavation depth. A three-level retaining wall is considered. A number of tasks have been solved. The depend values changing of displacement and internal effort on the redistribution of excavation levels is shown. Values are fixed in the characteristic points of the structural elements of retaining walls each level. Variables are different at level marks of retaining walls. The surfaces were created on bases of the obtained results. These surfaces are used to analyze the relationship between the heights of levels and the values of bending moments. Identified solutions lead to increased displacements in one or another level of retaining walls. The constitutive laws between the geometric parameters of the retaining walls and the stress-strain state of the system «retaining constructions – soil mass» are obtained.